PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR PADA BAYI USIA 1-6 BULAN - Tiara Pratiwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
Sleep and resting is one of the factors that influence the growth and development of children because when babies fall asleep, growth hormones are classified more threefold. According to the World Health Organization (WHO) included in the Pediatrics journal, around 33% of babies have problems sleeping in 2012. Baby massage is one way that can be used as one way to improve sleep quality baby. Analyze the influence of baby massage against sleep quality baby ages 1-6 months. This study was a pre-experimental with the design of One Group Pretest-Posttest Design. The population of this study is a baby aged 1-6 months. Research samples of 35 babies aged 1-6 months, taken accidentally sampling. The independent variable is a baby massage and dependent variable is sleep quality baby aged 1-6 month. The research instrument used a questionnaire that refers to the BISQ questionnaire which had previously been tested for validity by previous researchers. Data processing uses editing, coding, tabulating and Wilcoxon statistical test. The Results in the study showed that sleep quality babies aged 1-6 months before the baby massage are most babies have less good sleep quality of 11 (31,4%) and the quality of baby sleep ages 1-6 months after being given a baby massage stimulation have good sleep quality has increased by 20 babies (57.1%). Wilcoxon statistical test shows that the significant value of P Value = 0,000. This showed that there is an influence on infant massage against sleep quality baby aged 1-6 months